2021
DOI: 10.1007/s12070-021-02366-6
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction Among Asymptomatic Patients with SARS CoV2 Infection: A Case–Control Study

Abstract: Olfactory dysfunction (hyposmia, anosmia) is a well-recognized symptom in patients with coronavirus disease-19 (COVID-19). Studies of olfactory dysfunction in asymptomatic patients have not been reported. We conducted a study looking for the presence of olfactory dysfunction with an objective assessment tool in asymptomatic Covid 19 and compared it with patients with mild COVID-19 and age-matched controls. We recruited 57 male patients each of Mild COVID-19, asymptomatic Covid 19, and healthy controls for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…A total of 2113 abstracts were retrieved for screening, 114 full‐text articles were assessed for eligibility, and 50 studies 7 , 8 , 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 meeting inclusion criteria were selected in the qualitative synthesis. Data from 49 studies 7 , ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 2113 abstracts were retrieved for screening, 114 full‐text articles were assessed for eligibility, and 50 studies 7 , 8 , 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 meeting inclusion criteria were selected in the qualitative synthesis. Data from 49 studies 7 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the characteristics of included studies. 7 , 8 , 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 There were 16 case‐control studies 21 , 22 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Discerning the mechanism for the earliest changes in olfaction may be a key to early detection of SARS‐CoV‐2 infection. While self‐monitoring for smell loss is cost‐effective and easily implemented, research findings suggest that objective psychophysiological tests are more sensitive to COVID‐19 associated olfactory impairment than self‐report methods (Bagnasco et al, 2021; Gözen et al, 2020; Vaira et al, 2021) even in asymptomatic cases (Mangal et al, 2021; Vaira, Hopkins, et al, 2020). For example, a large multicenter study found that significantly more COVID‐19 positive participants were classified with olfactory dysfunction when tested with psychophysiological tests compared to self‐reported impairment (Vaira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%